Perlindungan Hukum Terhadap Korban Kekerasan Seksual Menurut Perspektif Hukum Pidana Islam - Uddin, Hafiz Rafi; Kristiono, Natal; R, Ruhadi (Media Hukum Indonesia (MHI), 2025)
Sexual violence is a serious problem that has a wide impact on victims, both physically and psychologically. In the legal context, there are differences in approach between Islamic criminal law and the positive legal system in Indonesia regarding victim protection. This study seeks to answer three problem formulations: how Islamic criminal law defines and provides protection for victims of sexual violence, the differences in protection between Islamic criminal law and the positive legal system in Indonesia, and the implementation of Islamic legal principles in a modern plural society. This study aims to examine legal protection for victims of sexual violence from the perspective of Islamic criminal law and compare it with the positive legal system. Using a literature study method, data were collected from fiqh books, the Qur'an, Hadith, scientific journals, and laws and regulations in Indonesia, which were then analyzed qualitatively. The results of the study show that Islamic criminal law offers protection based on divine justice with strict sanctions against perpetrators and restoration of victim honor, although the standard of proof is quite strict. On the other hand, Indonesian positive law provides a more flexible approach with a focus on victim rehabilitation and upholding human rights. In a plural society, the implementation of Islamic criminal law principles requires adaptation through ijtihad and integration of Islamic legal values with the positive legal system. This study concludes that combining the best elements of both legal systems can create comprehensive and responsive legal protection for victims of sexual violence.